The Role of Severe Vitamin D Deficiency in Predicting the Risk of Severe Exacerbation in Patients With Chronic Obstructive Pulmonary Disease - Zhou L; Han C; Zhou Y (International Journal of COPD)
Li Zhou,1– 4 Cunqiao Han,5 Yue Zhou1– 4 1Department of Emergency Medicine, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2West China School of Nursing, Sichuan University, Chengdu, People’s Republic of China; 3Disaster Medical Center, Sichuan University, Chengdu, People’s Republic of China; 4Nursing Key Laboratory of Sichuan Province, Chengdu, People’s Republic of China; 5Department of Emergency Medicine, Shangjinnanfu Hospital, West China Hospital, Sichuan University, Chengdu, People’s Republic of ChinaCorrespondence: Yue Zhou, Department of Emergency Medicine, West China Hospital, Sichuan University, No. 37 Guoxue Road, Chengdu, 610041, Sichuan, People’s Republic of China, Tel +86-028-62539203, Email zhouyuesccd@163.comBackground: This study aims to investigate the association between vitamin D levels and the risk of severe acute exacerbations of chronic obstructive pulmonary disease (AECOPD).Methods: We conducted a prospective observational study with 636 COPD patients admitted for exacerbations between January 2021 and December 2022. Patients were categorized based on serum 25-hydroxyvitamin D levels: severe deficiency (< 10 ng/mL), deficiency (10– 20 ng/mL), insufficiency (20– 30 ng/mL), or sufficiency (> 30 ng/mL). Severe exacerbation was defined when the patient visits an emergency room or is hospitalized due to COPD exacerbation. Multivariate Cox regression was used to evaluate the risk associated with vitamin D deficiency.Results: Over an 18-month follow-up, 178 (28.0%) patients experienced at least one severe exacerbation. The severe deficiency group had the highest exacerbation rate (40.6%), followed by deficiency (27.8%), insufficiency (22.5%), and sufficiency (18.1%) groups (P< 0.01). Multivariate Cox regression analysis showed that severe vitamin D deficiency was significantly associated with an increased risk of severe exacerbations (HR=2.74, 95% CI: 1.55– 4.84; P< 0.01) compared to vitamin D sufficiency.Conclusion: Severe vitamin D deficiency is a significant predictor of severe COPD exacerbations, highlighting the importance of routine vitamin D assessment and supplementation in COPD management.Keywords: acute exacerbations, COPD, risk factors, vitamin D deficiency